Effect of hypoxia on BOLD fMRI response and total cerebral blood flow in migraine with aura patients. Issue 4 (April 2019) - Arngrim, Nanna; Hougaard, Anders; Schytz, Henrik W; Vestergaard, Mark B; Britze, Josefine; Amin, Faisal Mohammad; Olsen, Karsten S; Larsson, Henrik BW; Olesen, Jes; Ashina, Messoud
Experimentally induced hypoxia triggers migraine and aura attacks in patients suffering from migraine with aura (MA). We investigated the blood oxygenation level-dependent (BOLD) signal response to visual stimulation during hypoxia in MA patients and healthy volunteers. In a randomized double-blind crossover study design, 15 MA patients were allocated to 180 min of normobaric poikilocapnic hypoxia (capillary oxygen saturation 70–75%) or sham (normoxia) on two separate days and 14 healthy volunteers were exposed to hypoxia. The BOLD functional MRI (fMRI) signal response to visual stimulation was measured in the visual cortex ROIs V1–V5. Total cerebral blood flow (CBF) was calculated by measuring the blood velocity in the internal carotid arteries and the basilar artery using phase-contrast mapping (PCM) MRI. Hypoxia induced a greater decrease in BOLD response to visual stimulation in V1–V4 in MA patients compared to controls. There was no group difference in hypoxia-induced total CBF increase. In conclusion, the study demonstrated a greater hypoxia-induced decrease in BOLD response to visual stimulation in MA patients. We suggest this may represent a hypoxia-induced change in neuronal excitability or abnormal vascular response to visual stimulation, which may explain the increased sensibility to hypoxia in these patients leading to migraine attacks.